Vocational work among young people: future vision - Pavlysh, V. A.; Pikh, Z. G.; Fedasyuk, D. V.; Zagorodniy, A. H.; Zakharyash, O. S.; Shakhovska, N. B.; Vasylyna, B. S. (Publishing House of Lviv Polytechnic National University, 2011)
The proceedings of Lviv Politechnic National University for the international exposition "Education and career – 2011" golden winner highlight the experience of implementation and usage of modern concepts in the sphere of vocational work among young people. Intellectual training and research centre of vocational and career education, established at the university, provides an educational mission of higher educational institution, the complex approach to best entrants selection, their training for entrance examinations; external testing and helps choose a profession consciously.